Local Stress Analysis in the Chain Link of Mooring Line That Had Diameter Degradation - Eko Budi Djatmiko; Murdjito Murdjito; Rafliansyah Azhar Putera (Department of Ocean Engineering, 2021)
Mooring systems are used to moored ships at a particular area. One of its type is SPM by using a buoy. The system generally uses chains used to tie buoys to the seabed. However, chains that are used continuously can experience degradation in the diameter of the chain connection. The degradation experienced by the connections between the chains will certainly affect the local ( von Mises stress). According to ABS rules, the amount of local stress or von Mises stress that occurs on an object must not exceed 90% of the yield strength of the material. Therefore, it is necessary to do a local stress analysis to determine the extent of degradation of the diameter of the chain connection so that the local stress value does not exceed that allowed. The largest mooring tension value that occurs in the mooring system is 1838,252 kN. The results show that if the chain connection is subject to a tension of 1838,252 kN, the diameter degradation that occurs in the chain connection must not exceed 15% of the initial diameter so that the local or von Mises stress does not exceed 369 MPa (90% of the yield strength of the material 410 MPa).